Virology, epidemiology, transmissions, diagnostic tests, prophylaxis and treatments of human Mpox: Saudi Arabia perspective - Almonther Abdullah Hershan (Frontiers in Cellular and Infection Microbiology)
Mpox (Monkeypox) is a highly contagious viral disease that can be transmitted from animal-to-human or human-to-human through intimate contact, Mpox is caused by the monkeypox virus (MPXV), which is an enveloped double-stranded DNA that belongs to the genus Orthopoxvirus, Poxviridae family, and subfamily Chordopoxvirinae. Mpox cases were previously only reported in West and Central Africa, however in recent times non-endemic countries including Saudi Arabia (SA) also reported confirmed Mpox cases. The first laboratory-confirmed human Mpox case in SA was reported on 14 July 2022, since then a number of confirmed Mpox cases have been reported by WHO in SA. These confirmed Mpox cases in SA were observed among individuals with a history of visiting European Union countries. SA is not only at risk of importation of Mpox cases owing to travel to such countries, but also there are various other risk factors including geographic proximity to the African continent, trade in exotic animals, and massive inflow of tourists. Therefore, government health authorities of SA should continue to collaborate with various international health organizations including WHO to prevent, manage or monitor potential health risks at most of the entry points in SA including highways, seaports, and airports by ensuring adherence to hygiene protocols, vaccinations, and health screenings. There are a range of diagnostic tests are currently available that can be used in SA to confirm Mpox infections, including real-time PCR, loop-mediated isothermal amplification, serological testing, clustered regularly interspaced short palindromic repeat-CRISPR-associated protein (CRISPR-Cas)-based systems, whole-genome sequencing, electron microscopy, and virus isolation and culture. There is no approved treatment specifically for Mpox, however multiple approved antiviral agents for smallpox treatment were found to be useful in Mpox treatment and in the management of Mpox outbreaks, such as- trifluridine, brincidofovir, tecovirimat, and cidofovir. The aim of this review is to provide valuable insights regarding virology, pathogenesis, epidemiology, transmissions, clinical presentation, diagnostic tests, prophylactic measures and therapeutic options of Mpox from SA perspective. Moreover, a side-by-side discussion on the global trend and scenarios of Mpox has been provided for comparison and further improvement in measures against Mpox in SA.